PENGARUH TAFSIR DAN KONDISI SOSIAL TAFSIR AHMAD HASSAN BANDUNG DALAM KHAZANAH KEILMUAN TAFSIR DI INDONESIA - Raisa Zuhra Salsabila Awaluddin; Aldy Pangestu (LPPM Sekolah Tinggi Agama Islam Darul Falah, 2022)
The result of this article is about the influence of nationalism that initially appeared in America and Western Europe and in Indonesia arose due to imperalism and colonialism. This led Ahmad Hassan to join a political party Persis (Persatuan Islam) to reject Nationalism, and criticized Sukarno as the father of modern nationalism. Hassan argued that Nationalism also separates Indonesia from the Qur'an that in other words religion is only a political view. The purpose of this article is to find out the influence of interpretation and social conditions that occurred in the time of Ahmad Hassan. The method used is to use Library Research because the sources used are books, articles related to Ahmad Hassan. Socio-intellectual influences also influenced Ahmad Hassan's Tafsir. The influence of Ahmad Hassan's Tafsir that appeared in Indonesia brought a new color in the scientific treasures of tafsir in Indonesia, which at first the interpretation in Indonesia used the pegon script, while this interpretation used Latin letters. The people of his day were guided only by the Tafsir Jalalain, making an important influence in the birth of Ahmad Hassan's interpretation.